Professionally Important Personal Qualities of Psychologists in Modern Foreign Researches - M.A. Odintsova; M.N. Raskhodchikova; E.I. Kuzmina (Современная зарубежная психология)
The article presents an analysis of modern foreign publications devoted to the study of professionally important personal qualities of psychologists, education psychologists and psychologists-consultants. Research has shown the complexity of the professional activity of a psychologist involving the solution of significant psychological issues, often not having clear work patterns. The key tasks that tackle psychologists are outlined: development and implementation of primary and secondary interventions, monitoring of educational and behavioral difficulties, counselling participants of educational environment, development and evaluation of psychological support programs, research activities, continuous improvement and validation of qualifications, work with critical situations. An attempt was made to analyze various approaches in the understanding of foreign researchers of the problem of professional identity. Professional identity is dynamic and variable, formed throughout life, unites emotional-will, value-semantic, personal features, begins with the choice of profession and continues throughout the professional life. The methods of diagnostics of professionally important personal qualities of psychologists developed by foreign researchers are described.